Sensitivity of Amazonian TOA flux diurnal cycle composite monthly variability to choice of reanalysis - Dodson, J Brant (Journal of geophysical research. Atmospheres : JGR, 2016)
Amazonian deep convection experiences a strong diurnal cycle driven by the cycle in surface sensible heat flux, which contributes to a significant diurnal cycle in the top of the atmosphere (TOA) radiative flux. Even when accounting for seasonal variability, the TOA flux diurnal cycle varies significantly on the monthly timescale. Previous work shows evidence supporting a connection between variability in the convective and radiative cycles, likely modulated by variability in monthly atmospheric state (e.g., convective instability). The hypothesized relationships are further investigated with regression analysis of the radiative diurnal cycle and atmospheric state using additional meteorological variables representing convective instability and upper tropospheric humidity. The results are recalculated with three different reanalyses to test the reliability of the results. The radiative diurnal cycle sensitivity to upper tropospheric humidity is about equal in magnitude to that of convective instability. In addition, the results are recalculated with the data subdivided into the wet and dry seasons. Overall, clear-sky radiative effects have a dominant role in radiative diurnal cycle variability during the dry season. Because of this, even in a convectively active region, the clear-sky radiative effects must be accounted for in order to fully explain the monthly variability in diurnal cycle. Finally, while there is general agreement between the different reanalysis-based results when examining the full data time domain (without regard to time of year), there are significant disagreements when the data are divided into wet and dry seasons. The questionable reliability of reanalysis data is a major limitation